2019
DOI: 10.1002/jhbp.691
|View full text |Cite
|
Sign up to set email alerts
|

Classification of pancreaticobiliary maljunction and its clinical features in adults

Abstract: Background In pancreaticobiliary maljunction (PBM), reflux of pancreatic juice and bile produces various pathological conditions in the biliary tract and pancreas. Clinical features according to the classification of PBM by confluence between the distal bile duct and the main pancreatic duct proposed in 2015 were evaluated in children. Methods Clinical features and complicating diseases according to the PBM classification were evaluated in 168 adult PBM patients. Patency of Santorini duct and associated biliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…4 PBM without biliary dilatation, (Type-B, as seen in our patient), are often asymptomatic and, therefore, usually diagnosed incidentally during adulthood, often concurrently with advanced biliary tract malignancy. 4 Due to its association with biliary cancers, the treatment recommendation for adults with PBM and CBD is extrahepatic bile duct resection. 3 The treatment recommendation for PBM without biliary dilatation remains contentious.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…4 PBM without biliary dilatation, (Type-B, as seen in our patient), are often asymptomatic and, therefore, usually diagnosed incidentally during adulthood, often concurrently with advanced biliary tract malignancy. 4 Due to its association with biliary cancers, the treatment recommendation for adults with PBM and CBD is extrahepatic bile duct resection. 3 The treatment recommendation for PBM without biliary dilatation remains contentious.…”
mentioning
confidence: 66%
“…Patients may present with intermittent abdominal pain, jaundice or an elevated amylase level. 1,4 When associated with CBD a classical triad of abdominal pain, jaundice and an abdominal mass has been described. 3 Children are more likely to be symptomatic from PBM regardless of subtype as are those with associated CBD.…”
mentioning
confidence: 99%
“…The diagnosis and treatment of GB lesions have been well discussed. [15][16][17][18][19][20][21] In particular, the differentiation between benign lesions and malignant lesions is a major issue of concern. Various approaches have been attempted for the accurate diagnosis of GB lesions including analysis of the enhancement pattern on contrast-enhanced US (CE-US) or contrast-enhanced EUS (CE-EUS).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and treatment of GB lesions have been well discussed 15‐21 . In particular, the differentiation between benign lesions and malignant lesions is a major issue of concern.…”
Section: Discussionmentioning
confidence: 99%
“…PBM is a congenital deformity in which the pancreatic and bile ducts unite anatomically outside the duodenal wall to form a long common channel [37]. It contributes to pancreatitis by causing a temporary or persistent obstruction of pancreatic juice or bile reflux into the pancreatic duct (biliopancreatic reflux) [38], followed by increased pressure in the pancreatic duct. A study found that PBM was one of the pathogenic factors of pancreatitis [39].…”
Section: Pancreatic Duct Visualizationmentioning
confidence: 99%